(untitled) (Psychocare, 2025)
Health issues are inseparable from mental health problems. Mental health is defined as a state of well-being in which individuals are able to recognize their potential, cope with daily life stressors, remain productive, and contribute to others. However, the surrounding environment often leads individuals into a less prosperous condition. As a community that encompasses relational aspects of life, Kapanewon Sedayu faces an urgent social problem, namely the stigmatization of people with mental disorders (ODGJ). This occurs due to the lack of understanding regarding mental disorders and their management. A mental health program in the form of psychoeducation and early detection pathways was designed as an effort to address mental health problems in Kapanewon Sedayu. Therefore, this community service aimed to provide knowledge and early detection skills related to mental disorders for prospective mental health cadres in Kapanewon Sedayu. The service method consisted of program coordination and socialization, the application of science and technology, and the enhancement of understanding and competence in early detection. The results showed that psychoeducation and early detection were effective in increasing residents’ understanding. Keywords: Early detection, mental health, Sedayu, psychoeducation